Subtotal hysterectomy of ischemic uterus during caesarean section in buffaloes - SINGH, M P; PRASAD, J K; DAS, ARUP KUMAR; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
Eight cases ofischemic/ necrosed uterus were detected during caesarean operation in buffaloes. Zone ofischemia was identified and quantified clinically in the gravid uterus during the operation. The percentage of ischemia / necrosis of the uterine bed ranged between 10 and 25%. After the manual removal of the dead foetus the portion ofischemic or necrosed uterus was excised along with the portion of peripheral healthy tissues of the gravid horn. Caesarean wound were closed routinely. One buffalo died but the other seven recovered uneventfully.